Overarching challenges to the implementation of competency-based medical education. (3rd June 2017) - Caverzagie, Kelly J.; Nousiainen, Markku T.; Ferguson, Peter C.; ten Cate, Olle; Ross, Shelley; Harris, Kenneth A.; Busari, Jamiu; Bould, M. Dylan; Bouchard, Jacques; Iobst, William F.; Carraccio, Carol; Frank, Jason R.; et al.
Abstract: Medical education is under increasing pressure to more effectively prepare physicians to meet the needs of patients and populations. With its emphasis on individual, programmatic, and institutional outcomes, competency-based medical education (CBME) has the potential to realign medical education with this societal expectation. Implementing CBME, however, comes with significant challenges. This manuscript describes four overarching challenges that must be confronted by medical educators worldwide in the implementation of CBME: (1) the need to align all regulatory stakeholders in order to facilitate the optimization of training programs and learning environments so that they support competency-based progression; (2) the purposeful integration of efforts to redesign both medical education and the delivery of clinical care; (3) the need to establish expected outcomes for individuals, programs, training institutions, and health care systems so that performance can be measured; and (4) the need to establish a culture of mutual accountability for the achievement of these defined outcomes. In overcoming these challenges, medical educators, leaders, and policy-makers will need to seek collaborative approaches to common problems and to learn from innovators who have already successfully made the transition to CBME.